Current Approaches to Addressing Burnout and Moral Injury: Experiences from Four Community Health Centers - Patricia Pittman; Samantha Meeker (Journal of Primary Care & Community Health)
Background: Burnout among Community Health Center (CHC) providers has worsened post-COVID-19, exacerbated by understaffing and heightened recruitment challenges due to competition from higher-paying hospitals and private practices. Objective: This exploratory qualitative study investigates strategies used by four leading CHCs to address perceived drivers of burnout among their providers. Methods: The study used qualitative interviews with CHC staff to explore approaches to mitigating burnout. Focus was placed on organizational strategies, staff engagement, and operational changes aimed at enhancing provider wellbeing. Results: Key challenges included low funding and rapid growth, leading to staffing shortages and strained relationships between staff and leadership. Common strategies to combat burnout involved: (1) emphasizing the CHC mission of supporting staff wellbeing, (2) creating onboarding and workforce development programs focused on support, (3) implementing operational changes to reduce workloads and maximize patient care time, (4) fostering staff involvement in decision-making, and (5) using wellness surveys with the expectation of visible changes based on feedback. Conclusion: The study found that employee voice is crucial in addressing burnout, contrasting with wellness approaches that focus solely on individual staff members. Involving staff in decision-making and addressing systemic issues are viewed by participants as essential strategies for mitigating burnout in CHCs.